"I've got a sheep with three legs if anybody wants it?": re-visioning the rural economy. Issue 8 (December 2015) - Crabtree, Andy; Chamberlain, Alan; Valchovska, Stela; Davies, Mark; Glover, Kevin; Greenhalgh, Chris
Abstract This paper reports on a study of 4CG, a cooperative enterprise located in rural Wales. 4CG operates for the good of the local economy and seeks to diversify its commercial portfolio through the creation of an online shop retailing goods and services from local suppliers. The paper compliments prior field studies focusing on rural enterprise and the challenges posed by this category of business for IT support. The current study is motivated by 4CG's interest in setting up a local online shop and explicates the organisational issues that this venture turns upon and elaborates for broader sustainability agendas.